Top-Tier Maternity and Children Specialist Smart Medical Care and Innovative 5G Outpatient Service Model - ChaoRong Guo; Hui Zhu; LiHua Zhou; YouQiong Liu (Complexity)
Purposes. Under the influence of big data, 5G technology, and the two-child policy, we are facing a shortage of medical resources, in short supply, and a substantial increase in demand for maternal and child health services. Medical needs improve patient experience, improve patient satisfaction, and apply smart medical care and 5G new model. Methods. Retrospective research methods and a large number of observation methods were used, and patient medical experience was improved through smart medical WeChat services, 5G technology, MDT (Multidisciplinary Team), one-stop services, and other measures. Research Results. Smart medicine and 5G models have effectively improved patient satisfaction and medical experience. Conclusions. Smart medicine meets the medical needs of women and children. 5G technology makes the medical model efficient and convenient and at the same time enhances the hospital’s core competitiveness.